IMPLEMENTASI PENCANANGAN KEBIJAKAN KAWASAN BEBAS KUMUH MELALUI HUNIAN MODEL RUSUNAWA (Rumah Susun Sederhana Sewa) DI KOTA PEKALONGAN - Siti As'adah Hijriwati; Siti Zulaekhah (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2012)
Abstract This research aims  to analyze  the implementation of rural  house complex policy, especially  strata  tittle,  in  order  word  condominium,  in  Pekalongan  City.  These policy has been implemented in order to fasilitate the minimum necessities of rural housing. There  are  some  problems  in  this  research.    First,how  does  the implementation of the rural housing complex, condominium policy in Pekalongan City?  Second,  what  problems  are    occured  because  of  this  policy?This  research typically descriptive-analyze. We want to describe all of local government policy in rural  house  complex  as  condominium  then  analize  them  until  results  the  real conclusion. In order to describe all,  socio legal method has been used. The rules of  these  policy  can  not  be  seen  unless  knowing  it’s  implementation  in  the  real human being life. All data, both primary and secondary also supported to dig out many  problems  of  crude  worker,  especially  sailormen  in  north  beach  of Pekalongan  Residence.  Data  searched  by    documentary  for  secondary  data  and interview  for  primary  data  in  other  side. This  research  concludes  that  there  are some  problems in the exsistence of this  rural house complex in vertical building named  ”Rusunawa”,  a  simple  housing    complex  with  the  rent  system.  Legal problem  shows  in  uncertainty  of  the  occupation.  Some  of  them  escapes  from  Rusunawa before they pay the rent cost. Keywords: rural housing complexs, rusunawa, condominium